PARP inhibitor olaparib increases the oncolytic activity of dl922‐947 in in vitro and in vivo model of anaplastic thyroid carcinoma - Passaro, Carmela (Mol Oncol, 2014)
PARP inhibitors are mostly effective as anticancer drugs in association with DNA damaging agents. We have previously shown that the oncolytic adenovirus dl922‐947 induces extensive DNA damage, therefore we hypothesized a synergistic antitumoral effect of the PARP inhibitor olaparib in association with dl922‐947. Anaplastic thyroid carcinoma was chosen as model since it is a particularly aggressive tumor and, because of its localized growth, it is suitable for intratumoral treatment with oncolytic viruses. Here, we show that dl922‐947 infection induces PARP activation, and we confirm in vitro and in vivo that PARP inhibition increases dl922‐947 replication and oncolytic activity. In vitro, the combination with olaparib exacerbates the appearance of cell death markers, such as Annexin V positivity, caspase 3 cleavage, cytochrome C release and propidium iodide permeability. In vivo, we also observed a better viral distribution upon PARP inhibition. Changes in CD31 levels suggest a direct effect of olaparib on tumor vascularization and on the viral distribution within the tumor mass. The observation that PARP inhibition enhances the effects of dl922‐947 is highly promising not only for the treatment of anaplastic thyroid carcinoma but, in general, for the treatment of other tumors that could benefit from the use of oncolytic viruses.